2245. Primary Central Nervous System Lymphoma in Patients with HIV and Non-HIV: Should We Treat Them Differently?. (26th November 2018) - Dandachi, Dima; Ostrom, Quinn; Chong, Insun; Bondy, Melissa; Serpa, Jose; Colen, Rivka; Morón, Fanny
Abstract: Background: Primary central nervous system lymphoma (PCNSL) is a rare type of non-Hodgkin lymphoma, mostly diffuse large B-cell type. In patients living with HIV (PLWH), PCNSL is associated with Epstein-Barr virus. The optimal diagnostic and prognostic tools, and treatment are yet to be defined. PLWH are typically excluded from prospective studies. The management of PCNSL is adopted from immunocompetent patients. Methods: We retrospectively reviewed 122 PCNSL cases presenting to MD Anderson Cancer Center from 2000 to 2016 ( n = 84) and Ben-Taub Hospital from 2012 to 2016 ( n = 38) to evaluate and compare the clinical characteristics, management, and clinical outcomes in patients with or without HIV infection. Results: Among 122 PCNSL cases, 21% had positive HIV test, of those, 89% had CD4 < 200 and 77% were not on antiretrovirals and not virally suppressed. PLWH were significantly younger (37 vs. 62 years. P < 0.01), and more likely to be African-Americans (61% vs. 7%; P < 0.01) and males (73% vs. 50%; P = 0.04) than non-HIV patients. There were no differences in presenting symptoms, ocular involvement, B-symptoms, and deep brain involvement. PLWH were more likely to have multiple brain lesions (69% vs. 44%, P = 0.02). Immunohistochemistry prognostic markers and the International Extranodal Lymphoma Study Group (IELSG) prognostic score were not different between HIV and non-HIV patients. Nevertheless, treatment strategies varied significantly. PLWH were more likely to receive whole brain radiation therapy as sole treatment (65% vs. 4%) and palliative care (12% vs. 2%), and less likely to receive chemotherapy (23% vs. 94%) ( P < 0.01). Also, 13% of the patients (all non-HIV) underwent autologous stem cell transplant. Most PLWH (88%) started antiretroviral therapy after diagnosis. Higher IELSG score was an independent predictor of mortality in multivariate regression analysis. The 2-year survival did not differ between PLWH and non-HIV patients [46% (30–72%) vs. 61% (52–72%) ( P = 0.12)]. Conclusion: Variation in the treatment of PCNSL between HIV and non-HIV patients is not fully explained by baseline characteristics and prognostic factors. More efforts are needed to identify causes underlying these disparities and ways to alleviate them. Disclosures: All authors: No reported disclosures.